2014
DOI: 10.1158/1538-7445.am2014-4766
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 4766: Pharmacodynamic and stratification biomarker for the anti-FGFR2 antibody (BAY1179470) and the FGFR2-ADC

Abstract: We are developing a novel fibroblast growth factor receptor 2 (FGFR2) directed antibody (BAY 1179470) as well as an FGFR2-antibody drug conjugate (FGFR2-ADC) for cancer therapy. FGFR2 is expressed in a range of tumor types such as gastric, breast, HNSCC, pancreatic and ovarian cancers. FGFR2 has been described to promote tumor growth and survival and play a role in chemotherapy resistance. In this study, we aim to identify stratification and pharmacodynamic biomarkers for two antibody-based anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The dominant strategy to target FGFR ectodomains is using monoclonal antibody/antibody-drug conjugate [93]. Several anti-FGFR monoclonal antibodies have been developed, and some of them are in clinical trials [94,95,96,97,98]. In addition, efforts have been made in the development of small molecule inhibitor targeting FGFR ectodomains.…”
Section: Current Status Of Small Molecule Fgfr Inhibitor Developmentmentioning
confidence: 99%
“…The dominant strategy to target FGFR ectodomains is using monoclonal antibody/antibody-drug conjugate [93]. Several anti-FGFR monoclonal antibodies have been developed, and some of them are in clinical trials [94,95,96,97,98]. In addition, efforts have been made in the development of small molecule inhibitor targeting FGFR ectodomains.…”
Section: Current Status Of Small Molecule Fgfr Inhibitor Developmentmentioning
confidence: 99%
“…Similarly, BAY 1179470 (developed by Bayer) is a human anti-FGFR2 monoclonal antibody. BAY 1179470 showed antitumor activity in gastric cancer xenograft models with high FGFR2 expression [100]. The anti-FGFR2 antibody BAY 1179470 is currently in Phase I testing in subjects with advanced, refractory solid tumors (Tables 5 and 6)…”
Section: Targeting the Fgf2/fgfr Pathway In Cancermentioning
confidence: 99%
“…Preclinical and phase I studies have suggested that these compounds have potent and selective anti-tumor activity against FGFRmutated cancers (80)(81)(82)(83). A recently developed monoclonal antibody against FGFR2 (BAY1179470) showed tumor suppressive potential in tumors with high FGFR2 expression (84). Phase I testing of this antibody just recently completed (NCT01881217).…”
Section: Fgfr2 Fusionsmentioning
confidence: 99%